2020
DOI: 10.1002/tea.21655
|View full text |Cite
|
Sign up to set email alerts
|

A curricular Delphi study to improve the science education of secondary school students in Spain

Abstract: A curricular Delphi study was carried out to help improve and develop scientific training for secondary school students in Spain. Using the Delphi method, the authors analyzed the degree of consensus among more than 100 stakeholders' answers to the question, “What aspects of science education are considered desirable for a (Spanish) citizen?” From their answers, the authors identified a set of five “concepts.” Of these, the most relevant was “Science education related to environmental issues and human health, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…It is imperative to provide comprehensive education to young individuals regarding all SDGs to enhance their comprehension of the fundamental principles and significance of these goals. This assertion has been previously acknowledged and emphasized by various scholars [73][74][75]. Unfortunately, recent research has indicated that the younger generation lacks adequate understanding pertaining to the SDGs.…”
Section: Discussionmentioning
confidence: 85%
“…It is imperative to provide comprehensive education to young individuals regarding all SDGs to enhance their comprehension of the fundamental principles and significance of these goals. This assertion has been previously acknowledged and emphasized by various scholars [73][74][75]. Unfortunately, recent research has indicated that the younger generation lacks adequate understanding pertaining to the SDGs.…”
Section: Discussionmentioning
confidence: 85%
“…A Delphi can be used to prioritise a set of characteristics or define issues that may have a range of interpretations by seeking consensus from experts over multiple rounds (Charro, 2020;McPhail & McNeill, 2019). A Delphi study usually involves no more than 30 participants who are experts in their field to form consensus regarding a topic or issue over, often, no more than three to four rounds (Ruppert & Duncan, 2017).…”
Section: The Delphi Methodsmentioning
confidence: 99%
“…Delphi methods can involve open-ended questions (Hatt, 2018) or quantitative measures of predetermined items (Irdayanti et al, 2015). The key elements to an effective Delphi is that the quality of participant expertise must be high (Charro, 2020), participation is anonymous (Neck & Corbett, 2018), and participants are given an opportunity to reflect on the overall results after each consecutive round (Bray et al, 2012).…”
Section: The Delphi Methodsmentioning
confidence: 99%
“…Avalan su empleo también numerosos estudios en el marco de la investigación educativa (Charro, 2020;Çetinkaya y Keser, 2018;López-Gómez, 2018;McIntyre-Hite, 2016; Mirata, Bergamin y Van der Westhuizen, 2020; Mohr y Shelton, 2017; Plesch, Kaendler, Rummel, Wiedmann y Spada, 2013; Pozzi et al, 2019;Yeh et al, 2014).…”
Section: Marco Empíricounclassified